Immunomodulatory Effects of Histone Deacetylation Inhibitors in Graft-vs.-Host Disease After Allogeneic Stem Cell Transplantation - Xu, Xiaoxiao; Li, Xiaoqin; Zhao, Yanmin; Huang, He (Frontiers in Immunology, 2021)
Histone deacetylase (HDAC) inhibitors are currently the most studied drugs because of theirwith beneficial effects on inflammatory response. Emerging data from numerous basic studies and clinical trials have showedn that histone deacetylaseHDAC inhibitors can suppress immune-mediated diseases, such as graft-versus-host disease (GVHD), while retaining beneficial graft-versus-leukemia (GVL) effects. These drugs prevent and/or antagonize treat GVHD by modifying gene expression and inhibiting the production of proinflammatory cytokines, regulating the function of allo-reactive T cells, and up-regulating the function and number of regulatory T cells. Some of these drugs may become a new immunotherapiesimmunotherapy for GVHD or and other immune diseases.